Metal-containing nanomaterials as lubricant additives: State-of-the-art and future development - Igor E. Uflyand; Vladimir A. Zhinzhilo; Victoria E. Burlakova (Friction)
Abstract This review focuses on the effect of metal-containing nanomaterials on tribological performance in oil lubrication. The basic data on nanolubricants based on nanoparticles of metals, metal oxides, metal sulfides, nanocomposities, and rare-earth compounds are generalized. The influence of nanoparticle size, morphology, surface functionalization, and concentration on friction and wear is analyzed. The lubrication mechanisms of nanolubricants are discussed. The problems and prospects for the development of metal-containing nanomaterials as lubricant additives are considered. The bibliography includes articles published during the last five years.